(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
In this work we use computational tools to model a monodisperse diluted colloidal suspension of permanently magnetized nanoparticles in carrier liquids that do not present magnetic properties. Three models are used to simulate repulsive forces acting on the particles, namely, the Screened-Coulomb potential based repulsive force, the classic Lennard-Jones potential based repulsive force and a electrostatic repulsion force that is meant to emulate the behavior of surfactants adsorbed onto the particle’s surface. The approaching of the particles submitted to these repulsive force models is examined. The suitability of each repulsive force model is determined based on its computational cost, the time necessary for particle approach and, finally, the way the particles do approach when submitted to it. We conclude that the Lennard-Jones repulsive force model is the most suitable for most computational applications. that require the particles not to form dimers, and the Screened-Coulomb potential based repulsive force is the most suitable for the situations where dimer/chain formation is desirable. The surfactant repulsive force model, although more expensive, allows one to examine the effects of parameters such as temperature and surfactant concentration on the particle’s approach and so might be most suitable for simulations that aim to optimize experimental procedures.